The relationship of nutrition in female infertility (Research, Society and Development, 2020)
Infertility is defined as the inability to obtain a pregnancy after 12 months or more of constant sexual intercourse without contraception, affecting approximately 8% to 15% of couples during their fertile lives. Some of the main causes of infertility are diseases like endometriosis; fibroids; ovulatory dysfunction; polycystic ovary syndrome and obesity, accompanied by lifestyle and environmental conditions, in which, stressful jobs; unbalanced nutrition and unhealthy diets contribute to interfering in the safety of reproduction in women and men. This study aimed to understand the relationship of nutrition as a determining factor in female infertility, in addition to the importance of micronutrient consumption, as well as the consequence of obesity and lifestyle in this process. The bibliographic search was carried out using the databases SCIELO, Google Scholar, PubMed, and articles published in the last ten years, national and international, were selected. After reviewing the literature, it was possible to analyze the consumption of micronutrients, antioxidants and an adequate lifestyle as factors that can significantly improve reproductive results, as well as the identification of the relationship between overweight and obesity individuals and their negative influence on women who are trying to conceive, in addition to habits such as smoking and drinking, act to delay conception and increase the risk of miscarriage.